Anthracycline Shunt Metabolites From Philippine Marine Sediment-Derived Streptomyces Destroy Cell Membrane Integrity of Multidrug-Resistant Staphylococcus aureus - Paderog, Melissa June V.; Suarez, Angelica Faith L.; Sabido, Edna M.; Low, Zhen Jie; Saludes, Jonel P.; Dalisay, Doralyn S. (Frontiers in Microbiology, 2020)
The rise of antibiotic resistance (ABR) and the drying up of the pipeline for the development of new antibiotics demands an urgent search for new antibiotic leads. While the majority of clinically available antibiotics were discovered from terrestrial Streptomyces, related species from marine sediments as a source of antibiotics remain underexplored. Here, we utilized culture-dependent isolation of thirty-five marine sediment-derived actinobacterial isolates followed by a screening of their antibacterial activity against multidrug-resistant S. aureus ATCC BAA-44. Our results revealed that the crude extract of Streptomyces griseorubens strain DSD069 isolated from marine sediments collected in Romblon, Philippines displays the highest antibacterial activity, with 96.4% growth inhibition. The S. aureus ATCC BAA-44 cells treated with crude extract of Streptomyces griseorubens strain DSD069 showed cell membrane damage as demonstrated by a) leakage and loss of vital cell constituents, including DNA and proteins, b) irregular shrinkage of cells, and c) increase membrane permeability. The antibiotic compounds were identified as Bisanhydroaklavinone and 1-Hydroxybisanhydroaklavinone with MIC value of 6.25 µg/mL and 50.00 µg/mL, respectively. Bisanhydroaklavinone and 1-Hydroxybisanhydroaklavinone are shunt metabolites in the biosynthesis of anticancer anthracycline derivatives namely doxorubicin, daunorubicin, and cinerubins. It is rare, however, that shunt metabolites are accumulated during fermentation of marine sediment-derived Streptomyces strain without genetic modification. Thus, our study provides evidence that natural bacterial strain can produce Bisanhydroaklavinone and 1-Hydroxybisanhydroaklavinone as antibiotic leads to combat ABR.